Safety requirements for cableway installations designed to carry persons - Ropes Part 6. Discard criteria (BSI, 2004)
Ropes, Passenger ropeways, Passenger transport, Cableways, Equipment safety, Safety measures, Transportation safety, Life (durability), Defects, Surface defects